Social and Spiritual Transformation in the Leadership of Prophet Yusuf: Sociological and Spiritual Analysis in Egypt in 16 BC - Salam, Rudi; Anwar, Azmiral; Nasution, Syawaluddin (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This research examines the social and spiritual transformation in the story of the Prophet Yusuf from a sociological perspective. The story of the Prophet Yusuf in the Koran is known to have a deep message and universal learning value. Prophet Yusuf inspired social and spiritual change with his empathetic actions towards the people around him. This research focuses on the final stage of social change implemented by the Prophet Yusuf after becoming the leader of Egypt. The research method used is content analysis with a phenomenological approach. This research shows that Prophet Yusuf as an agent of social change had strong leadership integrity. He inspires change by maintaining personal integrity, being a role model in honesty, forgiveness, and patience, and interacting with various levels of society. The process of social change carried out by Prophet Yusuf includes centrifugal methods (changing oneself first and influencing the people around him) and cultural diffusion (changing the culture of Egyptian society). This research concludes that the story of Prophet Yusuf provides insight into how social change can occur, namely through leadership integrity and cultural change. This story shows that social change can start from individuals who have strong vision and integrity, who then influence the community around them and spread the values of change through culture.